2007
DOI: 10.1002/prot.21387
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise prediction of conformational discontinuous B‐cell epitopes using the Mapitope algorithm

Abstract: Mapping the epitope of an antibody is of great interest, since it contributes much to our understanding of the mechanisms of molecular recognition and provides the basis for rational vaccine design. Here we present Mapitope, a computer algorithm for epitope mapping. The algorithm input is a set of affinity isolated peptides obtained by screening phage display peptidelibraries with the antibody of interest. The output is usually 1-3 epitope candidates on the surface of the atomic structure of the antigen. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 49 publications
0
83
0
Order By: Relevance
“…It has been suggested that amino acids that are proximal on the epitope act cooperatively, thus enhancing certain traits important for the binding interaction (Bublil et al, 2007;Enshell-Seijffers et al, 2003;Neuvirth et al, 2004). To test this hypothesis, the composition of amino acids was analyzed again, to check for overrepresentation of amino acid pairs (see Supplementary material for a detailed explanation of the statistical test).…”
Section: Amino Acid Cooperativity In Epitopesmentioning
confidence: 99%
“…It has been suggested that amino acids that are proximal on the epitope act cooperatively, thus enhancing certain traits important for the binding interaction (Bublil et al, 2007;Enshell-Seijffers et al, 2003;Neuvirth et al, 2004). To test this hypothesis, the composition of amino acids was analyzed again, to check for overrepresentation of amino acid pairs (see Supplementary material for a detailed explanation of the statistical test).…”
Section: Amino Acid Cooperativity In Epitopesmentioning
confidence: 99%
“…The Pepitope server (http://pepitope.tau.ac.il/) (Mayrose et al, 2007a) was used to map the selected peptides onto the 3D model of HA from A/swan/Poland/305-135V08/2006 (H5N1). Using the consensus methodology, both PepSurf (Mayrose et al, 2007b) and Mapitope algorithms (Bublil et al, 2007) were executed and their results combined into a single prediction including only residues predicted to be a part of the epitope in both algorithms. Mapping results were compared with the surface of the H5 HA structural model using UCSF Chimera (v1.11).…”
Section: Methodsmentioning
confidence: 99%
“…These include MIMOP [56], which predicts linear and conformational epitopes based on MimAlign and MimCons methods, MIMOX [57], Pepitope [58] which uses Pepsurf [59] and Mapitope [60] methods, Pep-3D-Search [61], and MimoPro [62] . These methods can be classified into two categories: sequencesequence alignment category and sequence-structure alignment category [63].…”
Section: Conformational B-cell Epitope Prediction Softwarementioning
confidence: 99%